Measurement of prompt Ds+-meson production and azimuthal anisotropy in Pb-Pb collisions at √sNN=5.02TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Kroesen, Martin; et al. (Physics letters, 2022)
The production yield and angular anisotropy of prompt Ds+ mesons were measured as a function of transverse momentum (pT) in Pb-Pb collisions at a centre-of-mass energy per nucleon pair sNN=5.02TeV collected with the ALICE detector at the LHC. Ds+ mesons and their charge conjugates were reconstructed at midrapidity (|y|<0.5) from their hadronic decay channel Ds+→ϕπ+, with ϕ→K−K+, in the pT intervals 2<pT<50GeV/c and 2<pT<36GeV/c for the 0-10% and 30-50% centrality intervals. For pT>10GeV/c, the measured Ds+-meson nuclear modification factor RAA is consistent with the one of non-strange D mesons within uncertainties, while at lower pT a hint for a Ds+-meson RAA larger than that of non-strange D mesons is seen. The enhanced production of Ds+ relative to non-strange D mesons is also studied by comparing the pT-dependent Ds+/D0 production yield ratios in Pb-Pb and in pp collisions. The ratio measured in Pb-Pb collisions is found to be on average higher than that in pp collisions in the interval 2<pT<8GeV/c with a significance of 2.3σ and 2.4σ for the 0-10% and 30-50% centrality intervals. The azimuthal anisotropy coefficient v2 of prompt Ds+ mesons was measured in Pb-Pb collisions in the 30-50% centrality interval and is found to be compatible with that of non-strange D mesons. The main features of the measured RAA, Ds+/D0 ratio, and v2 as a function of pT are described by theoretical calculations of charm-quark transport in a hydrodynamically expanding quark-gluon plasma including hadronisation via charm-quark recombination with light quarks from the medium. The pT-integrated production yield of Ds+ mesons is compatible with the prediction of the statistical hadronisation model.
Online verfügbar 24 Februar 2022, Artikelversion 4 März 2022
*ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, M.A. Völkl, B. Windelband [und 1004 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Im Titel ist der Buchstabe s tiefgestellt
Im Titel ist das Pluszeichen hochgestellt